Teaching materials used in the development of productive skills of the language in the english students - Ordoñez Barberán, Julio César (Machala : Universidad Técnica de Machala, 2016)
This project is focused on the teaching materials that the teacher can use with the students to develop the productive speaking and writing skills. the teaching materials are the resources that the teacher needs to guide the knowledge and improve the skills like speaking and writing in the students. the teaching material brings resources that facilitate the teaching learning process. commonly used within the educational environment to facilitate the acquisition of concepts, attitudes and skills in students of 3° year of bachelor "modesto chavez franco" high school. the method used in this project is the investigation. the present investigation wants to help teachers to discover its shortcomings and the origin of the same, to achieve a better student learning, therefore the development of this work is very vital to a correct teaching performance.
Keywords: ACQUISITION; PRODUCTIVE SKILL; SPEAKING; TEACHING MATERIAL; WRITING